A Poem as a Communiqué: the Communicativeness of Poetry of Onė Baliukonė - Barkutė, Skaistė (Respectus Philologicus, 2020)
This article presents the creation of art – a poesy – in the context of the theory of communication. Multimeaning of the concept of communication supposes plenty of attitudes and considerations and complexity of definition. There exist two different schools of communication studies, one being the process school and the other being the semiotic school. The process school is cantered on the transmission of messages and understanding the effects of it. The semiotic school focuses on communication being a production and exchanging of meanings. It researches how messages and texts interact with people. Since the creation of art is considered as communiqué, so its conveying content relates with, a spiritual link a creator and a perceiver. The article discusses a poem as a communiqué, its place in the structure of the process and semiotic communication models. The article also discusses poesy as a message and its communicativeness, informativeness, and importance. O. Baliukonė’s poetry was taken to implement this aim. The fulfilled research demonstrated that O. Baliukonė actively communicates with a reader through her poems. Decoding is the same creative process as encoding; thus, in this article, attention is paid to the poet’s and also to a reader’s creation of the meaning of a message.